The LIFE STREAMS Project for the Recovery of the Native Mediterranean Trout in Six Italian Pilot Areas: Planning and Adoption of Conservation Actions - Carosi, Antonella; Talarico, Lorenzo; Greco, Claudia; Vecchiotti, Antonia; D’Antoni, Susanna; Longobardi, Alessandro; Macchio, Stefano; Carafa, Marco; Casula, Paolo; Perfetti, Antonio; Amprimo, Paola; Rossetti, Alessandro; et al. (Biology (Basel, Switzerland), 2025)
The Mediterranean trout (currently referred to as Salmo ghigii for Corsican and Italian-native populations) is listed as Endangered in the IUCN Red List, due to fragmented distribution and declining populations across its whole range, and is included in Annex II of the European Habitat Directive. The widespread genome introgression from the invasive Atlantic trout (Salmo trutta), overexploitation, and habitat alterations represent major threats to the persistence of native populations. The LIFE18NAT/IT/000931 STREAMS project aims to enhance conservation status of Mediterranean trout in 6 Italian pilot areas (Maiella, Sibillini Mountains, Casentino Forests and Pollino National Parks, Montemarcello-Magra-Vara Regional Park, and Sardinia with five sites of the Natura 2000 Network), and in 19 transferability areas covering almost the whole Italian species range. To achieve this, the following conservation strategies were implemented: (i) the identification of residual native populations; (ii) eradication of entirely Atlantic-exotic populations and removal of hybrids in admixed populations; (iii) restocking/reintroduction of native populations; (iv) monitoring/improving the Mediterranean trout habitats quality; (v) production of the “Guidelines for the conservation and management of native Mediterranean trout and its habitat”; and (vi) the prevention of illegal stocking. Here, we present the project rationale, major outcomes on demographic and genetic characterization of wild populations, and summary results from conservation actions.